P102 Alternative splicing of the SLCO1B1 transporter in paediatric liver. Issue 6 (17th May 2019) - van Groen, BD; Bi, C; Gaedigk, R; Staggs, V; Tibboel, D; de Wildt, SN; Leeder, JS
Abstract : Background: Alternative mRNA transcripts occur in >90% of human genes and may be triggered by developmental signals. The hepatic transporter OATP1B1 (gene name SLCO1B1 ) traffics substrates across the hepatic membrane, and shows age-related changes in protein expression. We aimed to predict novel isoforms of OATP1B1 by studying alternative splicing of SLCO1B1 in human paediatric post-mortem liver tissue, and the relationship of their mRNA expression with age. Methods mRNA expression of SLCO1B1 transcripts was determined using RNA sequencing (HISAT2/StringTie). Novel mRNA transcripts were considered of relevance when (1) the expression was >5% of the annotated isoform, (2) it was a SLCO1B7 and SCLO1B1 hybrid transcript, or (3) when the expression was associated with age. The software packages ORF-finder, TMpred and TOPO2 were used to predict the protein sequence and structure of the novel isoforms. Relationship of expression with age was studied with the Kruskal-Wallis test for age groups (fetal, 0–1.5 year, 1.5–6 year, 6–12 year and 12–18 year) and with Spearman correlation tests for age on continuous scale. Results: In 97 hepatic post-mortem tissues (gestational age median 16.4 [range 14.7–41.3] weeks, postnatal age 0.36 [0 - 17] years) 27 novel mRNA transcripts were detected. Of these, 13 were relevant: 2 isoforms are predicted to translate into amino acid sequences similar to the annotated isoform for OATP1B1, 9 isoforms may translate into truncated versions, and the expression of 8 isoforms was associated with age. None of the isoforms had an ORF that covered the SLCO1B7 region. Conclusion: We showed that novel SLCO1B1 mRNA isoforms potentially translate into OATP1B1 protein with unknown function, and that alternative splicing may well be a regulatory mechanism for SLCO1B1 expression during development. This data provides a better understanding of age-related changes in the expression of OATP1B1, and, with that, potentially improves prediction of disposition of endogenous and exogenous substrates. Disclosure(s): BG was supported, in part, by the Ter Meulen fund 2018 provided by the Royal Dutch Academy of Sciences. The National Institute of Child Health and Human Development Brain and Tissue Bank for Developmental Disorders at the University of Maryland is funded by the National Institutes of Health (NIH) contract HHSN275200900011C, reference number, N01-HD-9-0011 and the Liver Tissue Cell Distribution System is funded by NIH contract number N01-DK-7-0004/HHSN267200700004C.